Pengaruh Kualitas Website Terhadap Pembelian Impulsif Konsumen Shopee Melalui Hedonic Shopping Motivation dan Utilitarian Value Sebagai Intervening (Survey pada Mahasiswa Universitas Sultan Ageng Tirtayasa) - Munandar, Imam (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2022)
This study aims to examine the effect of Website quality on impulsive purchases by including two intervening variables, hedonic shopping motivation and utilitarian value. This study uses a quantitative method with a survey approach. The research sample was taken as many as 100 people with a stratified random sampling technique on postgraduate students of Sultan Ageng Tirtayasa University. The data analysis used the SEM-PLS method with the outer model test stages, inner model testing and hypothesis testing. From the research results, it is known that. Website quality is proven to have a positive and significant effect on impulsive purchases; Website quality is proven to hcive a positive and significant infiuence on hedonic shopping motivation; Website quality is proven to have a positive and significant effect on utilitarian value, Hedonic shopping motivation has no effect on impulsive purchases; and Utilitarian value has a positive and significant effect on impulsive purchases, where the higher the utilitarian value, the higher the impulsive purchases of consumers using the Shopee application. From this study, it is known that 48.7% of impulsive purchases are infiuenced by other variables not examined in the model.